2014
DOI: 10.1017/thg.2014.34
|View full text |Cite
|
Sign up to set email alerts
|

Variants Close to NTRK2 Gene Are Associated With Birth Weight in Female Twins

Abstract: Low weight at birth has previously been shown to be associated with a number of adult diseases such as type 2 diabetes, cardiovascular disease, high blood pressure, and obesity later in life. Genome-wide association studies (GWAS) have been published for singleton-born individuals, but the role of genetic variation in birth weight (BW) in twins has not yet been fully investigated. A GWAS was performed in 4,593 female study participants with BW data available from the TwinsUK cohort. A genome-wide significant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
(47 reference statements)
0
15
0
Order By: Relevance
“…Overrepresented gene ontologies (GO) included regulation of protein homooligomerization, actin cytoskeleton reorganization, and GTPase mediated signal transduction ( Table S8 ). We also note that that several of these genes have been associated with weight in human GWAS, including Hmga2, Fto, and Ntrk2 ( Table S6 ) 2729 .…”
Section: Resultsmentioning
confidence: 83%
“…Overrepresented gene ontologies (GO) included regulation of protein homooligomerization, actin cytoskeleton reorganization, and GTPase mediated signal transduction ( Table S8 ). We also note that that several of these genes have been associated with weight in human GWAS, including Hmga2, Fto, and Ntrk2 ( Table S6 ) 2729 .…”
Section: Resultsmentioning
confidence: 83%
“…We specifically show that if a standard model, which considers only offspring genotypes, is fit to data generated under an underlying KIR–HLA-C interaction scenario, associations can be missed or identified incorrectly. These simulation results provide an explanation for why neither HLA-C nor KIR loci have been found to be significantly associated with birth weight in standard GWAS [22, 23], which fail to account for the effects of maternal genotypes. Similarly, if a single-locus QMFG test is used when 2 or more polymorphic loci are involved in the MFG interaction, power will likely be reduced.…”
Section: Discussionmentioning
confidence: 90%
“…Human maternal uNK receptors, which are encoded by the killer cell immunoglobulin-like receptor (KIR) gene family, can bind to human leukocyte antigens (HLA) expressed by fetal trophoblast cells thus forming an immune interaction between maternal and fetal cells [21]. Although other genes [22, 23] and environmental factors [24–27] are very likely to influence birth weight, there is evidence that this interaction between uNK KIR and trophoblast HLA influences the balance between restricted and amplified fetal placental cell invasion, transformation of spiral arteries, and, in turn, fetal development.…”
Section: Introductionmentioning
confidence: 99%
“…To explore the genetic variation’s influence on the association between DNA methylation of the target region of FGFR2 and FT-LBW, we identified 156 methylation quantitative trait loci (mQTLs) in relation to CpG 3 (cg22633036) and CpG 7 (cg25052156) through performing a look-up in an online catalog of mQTLs ( http://www.mqtldb.org ) [ 56 ]. None of the 156 identified mQTLs was associated with birth weight according to an online genome-wide association study (GWAS) catalog ( https://www.ebi.ac.uk/gwas ) [ 57 60 ], which suggested that the associations of CpG 3 (cg22633036) and CpG 7 (cg25052156) DNA methylation with low birth weight might not be confounded by shared genetic variations. However, it is worth to mention that the mQTLs in the online catalog were identified in cord blood which may not reflect the specific mQTL status in placental tissue; moreover, we cannot identify the mQTLs related to the other CpG sites uncovered by the Illumine 450k methylation array.…”
Section: Discussionmentioning
confidence: 99%